2019
DOI: 10.1080/17483107.2019.1568595
|View full text |Cite
|
Sign up to set email alerts
|

Cultural influences on perception of disability and disabled people: a comparison of opinions from students in the United Kingdom (UK) Pakistan (PAK) about a generic wheelchair using a semantic differential scale

Abstract: Assistive Technology (AT) product use occurs within a socio-cultural setting.The growth internationally in the AT product market suggests that designers need to be aware of the influences that diverse cultures may have on the societal perception of an AT product through its semantic attributes. The study aimed to evaluate the visual interaction with an AT product by young adults from Pakistan, a collectivist society, and the United Kingdom (UK), an individualist society. A paper-based questionnaire survey was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 49 publications
(109 reference statements)
2
13
0
1
Order By: Relevance
“…This behaviour of self-dependence of Hong Kong participants is quite similar to the individualistic society while considering the other group as a collectivist society. The nomenclature of this segregation (individualistic and collectivist society) has also been found operative in a similar study (Asghar et al, 2019). The comparison of the mean value of both cultural groups has also depicted that the level of environmental familiarity is quite higher in Pakistani participants owing to ample environmental knowledge from signage and verbal directions.…”
Section: Cultural Differencessupporting
confidence: 67%
See 1 more Smart Citation
“…This behaviour of self-dependence of Hong Kong participants is quite similar to the individualistic society while considering the other group as a collectivist society. The nomenclature of this segregation (individualistic and collectivist society) has also been found operative in a similar study (Asghar et al, 2019). The comparison of the mean value of both cultural groups has also depicted that the level of environmental familiarity is quite higher in Pakistani participants owing to ample environmental knowledge from signage and verbal directions.…”
Section: Cultural Differencessupporting
confidence: 67%
“…Hong Kong has an influence from Western culture owing to which bilingual Hong Kong participants can be considered close to an individualistic society (Ralston et al, 1995). On the other hand, Pakistan being influenced by collective culture can be observed as a collectivist society owing to strong social relationships and interdependence (Asghar et al, 2018(Asghar et al, , 2019. For the present study, significant cultural influences have been observed in wayfinding behaviours for both cultural groups.…”
Section: Discussionsupporting
confidence: 45%
“…Emotions at the visceral level often occur before the person has actually interacted with the product in any meaningful way, but they can determine how much a person is willing to "forgive" in terms of usability, cost and other practical considerations [38]. Interestingly, studies have shown that visceral responses linked to aesthetic considerations of assistive devices such as wheelchairs seem to be more important in collectivist societies, such as Kenya, compared to individualist societies which are typical of Western countries [5].…”
Section: Emotional Designmentioning
confidence: 99%
“…According to the World Health Organization (WHO) report, ten (10) percent (one billion people) of the world population has some sort of disability [2]. The increase in prevalence of disability and number of elderly people, resulted in the growing demand of associated products for disabled people or formally termed as Assistive Technology (AT)…”
Section: Introduction: Disability Society and Assistive Technology (A...mentioning
confidence: 99%
“…products [1,[3][4][5][6][7][8][9][10]. The frequently cited and internationally accepted definition for the AT products is "any item, piece of equipment, or product system, whether acquired commercially off the shelf, modified, or customized, that is used to increase, maintain, or improve functional capabilities of individuals with disabilities" [11,p.17].…”
Section: Introduction: Disability Society and Assistive Technology (A...mentioning
confidence: 99%